THE TASK OF EDUCATORS IN THE KORAN - Ibrahim Hasan (Proceeding International Seminar of Islamic Studies, 2021)
The background of this study is The paradigm in educational issues as found in the Koran has not been fully understood and practiced by an educator.This shows that there is still a gap between the practice of educators and the teachings in the Koran. Where in practice, not a few are the source of the problem.The reality in field shows that some of them are less able to carry out their duties and responsibilities properly.Besides that, there are no references discusses the concept of educators, especially the task of educators in the Koran.The study aimed to analyze the task of educators contained in the Koran. The results of this study are expected to add new perspectives to implement the tasks of educators contained in the Koran. The study was library research, using an interpretive science approach, which was trying to see the educators' tasks contained in the Koran. Data were the verses of the Koran as the primary data source and other supporting books related to the object of research as a secondary data source. Data were collected by the documentation method and analyzed using the maudu’i, tahlilymethod, comparison, and interpretation. The results found that there were educators' tasks in the Koran, namely: First, tazkiyah al-nafs (purifying oneself) includes purification of thoughts or aqidah, deeds, hearts, and assets. Second, tarbiyah (educate) includes education of the body and spirit. Third, ta’lim (teaching) includes teaching al-Kitab(Koran) and al-Hikmah (Hadis), teaching an unknown science, teaching al-Bayan, and teaching the skills of making armor. Fourth, yatluAyatillah (reciting the verses of Allah) includes reading the verses of qauliyah (Alquran) and verses of kauniyah (the universe).Fifth, yursyid (guiding), Sixth, yad'unaila al-khair (Inviting only the good). Keywords: Task. Educator, Koran